Which Dengue Vaccine Approach Is the Most Promising, and Should We Be Concerned about Enhanced Disease after Vaccination?: The Challenges of a Dengue Vaccine - Screaton, Gavin (Cold Spring Harb Perspect Biol, 2018)
A dengue vaccine has been pursued for more than 50 years and, unlike other flaviviral vaccines such as that against yellow fever, progress has been slow. In this review, we describe progress toward the first licensed dengue vaccine Dengvaxia, which does not give complete protection against disease. The antibody response to the dengue virion is reviewed, highlighting immunodominant yet poorly neutralizing responses in the context of a highly dynamic structurally flexible dengue virus particle. Finally, we review recent evidence for cross-reactivity between antibody responses to Zika and dengue viruses, which may further complicate the development of broadly protective dengue virus vaccines.